Precision and kinetics of adaptation in bacterial chemotaxis - Meir, Yigal; Jakovljević, Vladimir; Aliaksiuk, Volha; Sourjik, Victor; Wingreen, Ned S. (Biophysical journal, 2010)
The chemotaxis network of the bacterium Escherichia coli is perhaps the most studied model for adaptation of a signaling system to persistent stimuli. Although adaptation in this system is generally considered to be precise, there has been little effort to quantify this precision, or to understand how and when precision fails. Using a Förster resonance energy transfer-based reporter of signaling activity, we undertook a systematic study of adaptation kinetics and precision in E. coli cells expressing a single type of chemoreceptor (Tar). Quantifiable loss of precision of adaptation was observed at levels of the attractant MeAsp as low 10 μM, with pronounced differences in both kinetics and precision of adaptation between addition and removal of attractant. Quantitative modeling of the kinetic data suggests that loss of precise adaptation is due to a slowing of receptor methylation as available modification sites become scarce. Moreover, the observed kinetics of adaptation imply large cell-to-cell variation in adaptation rates—potentially providing genetically identical cells with the ability to “hedge their bets” by pursuing distinct chemotactic strategies.
Gesehen am 13.04.2023